Manufacturing of stereolithographic 3D printed boron nitride nanotube-reinforced ceramic composites with improved thermal and mechanical performance. (1st March 2023) - Tank, Mehul; Leon, Ana De; Huang, Winton; Patadia, Mitesh; Degraff, Joshua; Sweat, Rebekah
Abstract: Boron nitride nanotubes (BNNTs) are the perfect candidate for nanofillers in high-temperature multifunctional ceramics due to their high thermal stability, oxidation resistance, good mechanical properties, high thermal conductivity, and radiation shielding. In this paper, 3D printed ceramic nanocomposite with 0.1 wt% of BNNT was prepared by fusing it at high temperatures. Samples were built with three different print directions to study the effect of print layers on mechanical performance along with BNNT addition. Dynamic mechanical analysis is performed to study the length effect of nanoscale reinforcements on the mechanical properties of the printed ceramic composites reporting significant improvements up to 55% in bending strength and 72% in bending modulus with just 0.1 wt% BNNT addition. A 63% thermal diffusivity improvement of ceramic by adding BNNTs is observed using laser flash analysis. The bridging and pull-out effect of nanotubes with a longer aspect ratio was observed with high-resolution microscopy. Such composites' modeling and simulation approaches are crucial for virtual testing and industrial applications. Understanding the effect of nanoscale synthetic fillers for 3D printed high-temperature ceramics can revolutionize future extreme environment structures.